Differences in Self-Esteem of Bullies and Victims of Bullying In Class VIII Students at SMPN 56 Bandung - Nurhayati, Eti (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
Adolescence is a time of developing self esteem which is his identity. Each individual's self esteem is different, this is influenced by the individual's perspective in interpreting each experience, including experience bullying. Bullies and victims of bullying will have different levels of self esteem, because each individual has a different self-assessment. So the purpose of this study was to examine the difference in levels of self esteem of victim of bullying and bullies in class VIII students at SMP Negeri 56 Bandung. The method used in this research is descriptive comparative research with a quantitative approach. The subjects of this study were students of class VIII SMP Negeri 56 Bandung. Data collection techniques carried out by researchers using psychological questionnaires self esteem which has gone through validity and reliability tests. In the validity test, 40 items were declared valid and 8 items were declared invalid. The sampling technique was purposive sampling, so that students who were selected according to the criteria in this study were 8 victim of bullying and 6 bullies. The data analysis technique used in this study is the Mann-Whitney test. The results of this study indicate the value of Asymp. Sig. (2-tailed) of 0.01 <0.05. Then it can be stated that Ho is rejected and Ha is accepted. This it can be said that there are differences in levels of self esteem for victim of bullying and bullies.